Estudio de los daños y refuerzos necesarios para la recuperación del techo de la iglesia de Salsipuedes-Córdoba-Argentina - Gómez, J. L.; Klein, K.; Montiel, G. (Revista ALCONPAT, 2014)
Salsipuedes The Church of the Province of Cordoba was built in 1875 and its roof is formed by a wooden structure, reticulate beams and straps which support ceramic arches tile mortar layer and tiling Legguards The Church is disabled as a precaution due to the appearance of cracks in the grid bars and breaking away of pieces of masonry near the support of the main beams. In this work we study the stress state of the grid bars and support the realization of the main beams in the masonry walls. Confirmed the high value of the working stresses of the bars with pathological manifestations, as well as inadequate support system in the masonry, projecting reinforcements necessary for safe operation of the structure with a degree of security. .Keywords: Wooden structures, pathology, patrimony